2006
DOI: 10.1074/jbc.m606555200
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal Lobes of Both Regulatory Light Chains Interact with the Tail Domain in the 10 S-inhibited Conformation of Smooth Muscle Myosin

Abstract: In the presence of ATP, unphosphorylated smooth muscle myosin can form a catalytically inactive monomer that sediments at 10 Svedbergs (10 S). The tail of 10 S bends into thirds and interacts with the regulatory domain. ADP-P i is "trapped" at the active site, and consequently the ATPase activity is extremely low. We are interested in the structural basis for maintenance of this off state. Our prior photocross-linking work with 10 S showed that tail residues 1554 -1583 are proximal to position 108 in the C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 62 publications
1
20
0
1
Order By: Relevance
“…This evidence however is insufficient to directly demonstrate that 10S exists, as other forms of SMM, such as small filaments would likely behave in a similar manner. We characterized Peptide A that destabilized the 10S conformation by a mechanism that is consistent with the extensive structural information about the head-tail interaction in 10S SMM (8,24,25) (Fig. 4A).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This evidence however is insufficient to directly demonstrate that 10S exists, as other forms of SMM, such as small filaments would likely behave in a similar manner. We characterized Peptide A that destabilized the 10S conformation by a mechanism that is consistent with the extensive structural information about the head-tail interaction in 10S SMM (8,24,25) (Fig. 4A).…”
Section: Discussionsupporting
confidence: 70%
“…4A) derived from the sequence of the SMM HC immediately N-terminal of the head-tail junction (position of the invariant proline) including the RLC binding motif. We have previously shown that in the 10S conformation both the N-and C-terminal lobes of the RLC interact with Bend 2 in the light meromyosin (LMM) region of the SMM tail (24,25) (Fig. 4A).…”
Section: Smm Pools Can Be Partially Interconverted In α-Toxin-permeabmentioning
confidence: 99%
“…Sample preparation and trypsin digestion procedures for mass spectrometry and mass spectral data analysis were essentially as described (18). Some of the digests were applied to a C18 PepMap 100 column (Dionex) and chromatographed using a gradient from 2% acetonitrile, 0.1% formic acid, to 80% acetonitrile, 0.08% formic acid on an UltiMate 3000 Nano LC System (Dionex) attached to a Probot microfraction collector (LC Packings) spotting sample directly to a MALDI plate in 7 mg/ml ␣-cyano-4-hydroxy-cinnamic acid supplemented with 2% (wt/wt) ammonium citrate in 75% acetonitrile.…”
Section: Methodsmentioning
confidence: 99%
“…Internal standards were insulin B-chain and angiotensin 1-7 clip. The sequence of the dimeric head ϩ G234A ϩ S188C cross-linked to the tail construct containing residues 823-944 was confirmed by tandem mass spectrometry as described (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation